Influence of γ-Irradiation on the Electronic Structure and the Chemical and Mechanical Properties of Poly(hydroxybutyrate-valerate)/Poly(caprolactone) Blends: Insights from Experimental Data and Computational Approaches - Francisco Rosario; João Paulo Almirão de Jesus; Suzan Aline Casarin; Felipe de Almeida La Porta (Nanomanufacturing, 2024)
In this study, we investigated the influence of γ-irradiation (0, 50, and 100 kGy) doses on the chemical and mechanical properties of biodegradable poly(hydroxybutyrate-valerate)/poly(caprolactone) (PHBV/PCL) polymer blends rich in low-molar-mass PCL, which were prepared using a co-rotating twin-screw extruder. In parallel, the density functional theory (DFT) and the time-dependent DFT (TD-DFT) methods were used together with a model containing four monomer units to provide an insight into the electronic structure, chemical bonds, and spectroscopic (such as Nuclear Magnetic Resonance (NMR) and Ultraviolet-visible (UV-vis)) properties of PHBV and PCL blend phases, which are critical for predicting and designing new materials with desired properties. We found that an increase in γ-irradiation doses caused splitting instead of crosslinks in the polymer chains, which led to evident deformation and an increase in tensile strength at break of 2.0 to 5.7 MPa for the PHBV/PCL blend. Further, this led to a decrease in crystallinity and proved the occurrence of a more favorable interaction between the blend phases.